Technology-Mediated TBLT on Student's ‎Confidence and Motivation - Rosyidah, Ummu; Faladiba, Muthia Nadhira (IKIP Siliwangi, 2025)
The abrupt transition to online instruction due to the COVID-19 pandemic has prompted educators to implement a wide range of innovative teaching strategies. This scenario becomes even more complex when English is taught as a supplementary subject in the first year of pharmacy programs. A primary concern in online English language instruction is how to maintain student engagement and encourage continued use of the target language. However, understanding students' learning motivation is a crucial factor in establishing a conducive environment that will motivate them to continually study English and achieve proficiency in the four language skills. This study aimed to determine whether interactive, technology-mediated task-based language teaching can enhance students' motivation and confidence and explore their perceptions of the tasks. Employing a qualitative approach, the study relied on observations and questionnaires as the primary data collection methods. The findings demonstrate that interactive, technology-mediated tasks significantly increase students' motivation and confidence for learning English. Additionally, the paper provides examples of how technology-mediated tasks can be designed to promote learners' productive use of English. Finally, the study discusses some anticipated challenges in implementing technology-mediated task-based language teaching in online instructional contexts.